Rego and Polikoff strike songbook, 1929 (1929)
1929 1918-1939 "Rego and Polikoff strike songbook, 1929" [T0133.jpg], 1929, United Clothing Workers Union In 1928, 600 young women from the Rego Clothing Factory in Edmonton, North London, come out on strike over piecework payments which escalated into a strike over union recognition. The strike was not supported by the Tailors' and Garment Workers Union, which sacked its London organisers, Sam Elsbury for associating with the communist party and the National Minority Movement (NMM). (Elsbury and c10% of the strikers were Communist Party members). Elsbury started a breakaway union, the United Clothing Workers' Union (UCWU). 700 workers at Polikoffs, one of London's largest clothing firms struck for recognition of the new union in 1929 but failed. Thereafter the UCWU declined and was disbanded in 1935.